The Impact of Crew Resource Management Training on Operational Skill of Aircraft Operation Student: A Comparison Between Simulation-Based and Theoretical Learning - Rico Darmawan; Fajar Islam; Prasetyo Iswahyudi; Kukuh Tri Prasetyo (Research Synergy Press, 2025)
Crew Resource Management (CRM) is a critical training method in aviation aimed at improving teamwork, communication, risk management, and decision-making to minimize human error, a significant contributor to aviation accidents. While theoretical training builds foundational knowledge, it often lacks practical application necessary to develop operational skills in real scenarios. This study compares CRM training through simulation using the FLOPS Simulator with traditional theoretical instruction, focusing on their impact on Aircraft Operations students’ skills. This quasi-experimental study investigated the effects of theoretical and simulation-based CRM training on operational skills among 24 Aircraft Operations students. Initial CRM knowledge was assessed through a theory test, followed by a first simulation to evaluate students practical CRM skills. Observations and interviews captured their challenges and experiences. A second simulation assessed improvements in operational skills, with data analyzed using descriptive statistics and qualitative insights from interviews. Results indicate that simulation-based CRM training significantly enhances operational skills, particularly in communication, teamwork, risk management, and decision-making, compared to theoretical training. Simulation provides a more immersive learning experience, allowing the application of CRM principles in near-real operational conditions. This study, conducted at a single institution, highlights the need for broader research involving multiple institutions and long-term assessments to further validate findings. By addressing gaps in CRM training, this research underscores the effectiveness of simulation in aviation education and its potential to improve CRM training practices